A coupled excavation and rainfall-induced loess landslide in Liuwanjia Village, Yan'an China: Case study of Middle Pleistocene loess slopes. (October 2019) - Fan, Zhongjie; Meng, Zhenjiang; Ren, Hongyu; Peng, Jianbing; Pei, Xiangjun; Dong, Linyao; Du, Jun; Zhang, Hongya
Abstract: Loess Plateau is one of the natural test sites to carry out the research of hazards induced by human activities. The loess landslide at Liuwanjia, Yan'an City, Shaanxi Province of China was observed to occur after continuous excavation and rainfall. The Liuwanjia landslide was selected as a case study and then detailed field mapping, 3D laser scanning and laboratory tests were carried out to study the formation characteristics and mechanism of this type of landslide. Based on the analysis of field investigation, excavation was a direct causing factor and the rainwater was a significant influencing factor in the formation of the landslide. The unloading fissures caused by excavation were preferential paths for infiltration of rainwater. Soil compression in the slope induced by excavation and the infiltration of rainwater played an significant role in the formation of local failure. Finally, the formation mechanism of Liuwanjia landslide has been discussed.